2014
DOI: 10.1186/1756-3305-7-43
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with recombinant Brugia malayi cystatin proteins alters worm migration, homing and final niche selection following a subcutaneous challenge of Mongolian gerbils (Meriones unguiculatus) with B. malayi infective larvae

Abstract: BackgroundCysteine protease inhibitors of Brugia malayi have been ascribed to be involved in parasite development as well as to immunomodulate the host’s immune response. In Onchocerca volvulus, Onchocystatin has been shown to induce partial protection in the mouse diffusion chamber vaccination model. In the present study we investigated the impact of vaccination with recombinant Bm-CPI-1 and Bm-CPI-2 proteins on protection against a subcutaneous challenge of B. malayi third stage larvae in gerbils.FindingsVac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…heart and lung instead of lymphatics. As never previously reported in the literature that a vaccine induced selection of parasite' habitat, the investigators recommended further studies to explain this unique rare phenomena [205] .…”
Section: Cystatins (Cyss)mentioning
confidence: 86%
“…heart and lung instead of lymphatics. As never previously reported in the literature that a vaccine induced selection of parasite' habitat, the investigators recommended further studies to explain this unique rare phenomena [205] .…”
Section: Cystatins (Cyss)mentioning
confidence: 86%
“…malayi have been developed as recombinant proteins and also evaluated for their immunoprophylactic effectiveness [3, 27, 28] with varied success. Our earlier studies demonstrated moderate to high protective efficacy in some of the recombinant B .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that vaccination of gerbils with recombinant Bm -CPI-1 or -2 did not confer protection against B. malayi infection but rather altered the site of establishment of the developed adult worms, causing an increase in their residence in heart and lungs instead of lymphatic vessels (Arumugam et al, 2014). The reason for the lack of protective efficacy of the native Bm -CPIs vaccine is unclear, but it could be related to the known immunomodulatory property of cystatins, especially Bm -CPI-2.…”
mentioning
confidence: 99%
“…Fertility was determined by measuring the levels of microfilariae (MF) in gerbil blood and by performing embryograms of female worms. The total number of worms recovered was recorded, male and female worms were differentiated and tissue location was noted upon harvest from heart, lung and various lymphatic organs as previously described (Arumugam et al, 2014). Female worm length was measured under an Olympus MVX10 microscope using the Olympus DP2-BSW software.…”
mentioning
confidence: 99%
See 1 more Smart Citation